The Guidelines for Development of the Organizational Health of Schools Under the Kalasin Primary Educational Service Area Office 2 - Raksuttee, Sompong; Phoojomjit , Pongphop (Interdisciplinary Academic and Research Journal, 2024)
Background and Aims: The organizational health of schools was conditions of operations according to the mission of schools. schools can survive and develop continuously, problem-solving, smooth internal administrative processes, and no stress. Therefore, this research aims to study the current state, the desirable state, and the priority needs and study the guidelines for the development of the organizational health of schools under the Kalasin primary educational service area office 2. Methodology: The research is divided into 2 phases: Phase 1 studies the current state, desirable state, and priority needs of development and the organizational health of schools, A sample group of 278 school administrators and teachers, was randomly selected using a stratified sampling method. The research instrument is a questionnaire with a 5-level with a confidence value of 0.81 and data analysis by mean and standard deviation. phase 2 study of the guidelines for the development of the organizational health of schools. The target group comprises 3 best practice schools and 9 experts for assessment of the development guideline. The research instrument was a semi-structured interview form and assessment form the suitability and feasibility of development guidelines. Results: The current state overall was moderate level, and the desirable state overall was at the highest level. The priority needs ranked from high to low level were teacher friendliness, colleague leadership, morale, communication, and resource utilization respectively. The development guideline of organizational health of schools under the Kalasin primary educational service area office 2 was a method for developing using a manual consisting of 1) principles and reasons 2) objectives, 3) content 4) development methods 5) measurement and evaluation. The development guidelines are divided into 6 learning units: 1) resource utilization, 2) teacher friendliness, 3) communication, 4) morale 5) colleague leadership. The results of the evaluation of the suitability and feasibility of development guidelines overall were at the highest level. Conclusion: Organizational health Organizational health is important for schools, administrators, teachers, educational personnel, and students. Because of the quality and efficiency in schools organization on the organizational health. Organizational health consists of factors, resource utilization, teacher friendliness, communication, morale, and colleague leadership.